Biochemical and Physicochemical Changes in Spaghetti Meat During Refrigerated Storage of Chicken Breast - Tasoniero, Giulia; Zhuang, Hong; Bowker, Brian (Frontiers in Physiology, 2022)
This study investigated postmortem muscle protein degradation and myowater properties in broiler breasts afflicted with the Spaghetti Meat (SM) myopathy during 7 days of storage. Severe SM and unaffected (NORM) breast fillets were analyzed at days 0, 3, and 7 postmortem for TD-NMR myowater traits, myofibrillar protein profiles, calpain activity, free calcium, and desmin and troponin-T degradation patterns. Only at day 0, muscle histology, fiber size and sarcomere length were assessed on multiple fillet portions. In SM breasts, the intramyofibrillar water population exhibited longer relaxation times (P = 0.0172) and a lower proportion (P = 0.0118) compared to NORM. SM had a greater proportion of extramyofibrillar water (P = 0.0080) possessing a longer relaxation time (P = 0.0001). Overall, the SM myopathy had only a minor impact on the myofibrillar proteins profiles and did not affect either free calcium concentration, calpain activity, or the degradation of desmin and TnT, while storage time strongly affected all the traits measured. At microscopic level, muscle tissue from SM fillets exhibited the typical indicators of myodegeneration mostly in the superficial-cranial portion of the breast, while fiber size and sarcomere length were similar between the two muscle conditions irrespectively from the portion considered. The lack of overall significant interaction effects between muscle condition and storage period suggested that SM and NORM breast meat experience similar proteolytic and physical changes during the postmortem period.